Global handbook on noncommunicable diseases and health promotion - McQueen, David V. (Springer, 2013)
Here is an important resource for understanding and approaching chronic illnesses and their prevention. This text balances theory and strategies to provide an integrative context for health-affecting behaviors regarding smoking, diet, and physical activity